PENGEMBANGAN PARIWISATA BERBASIS PARTISIPASI MASYARAKAT (STUDI KASUS: PANTAI UNGAPAN KABUPATEN MALANG) - Risa Amalia Kurniawati (Journal of Tourism Destination and Attraction, 2022)
Tourism development aims to increase local income. One example of tourism development is in Ungapan Beach, Malang Regency. The potential in Gedhangan District, Malang Regency has its uniqueness compared to other beaches in Malang Regency, therefore tourism development requires community participation. To further develop Ungapan beach tourism, the Malang Regency government also involves community participation. One of the things that the Malang Regency government has done is to involve and develop the UMKM sector. This is done to channel the spirit of regional potential-based tourism development to the people of Malang Regency. The role of the surrounding community in tourism development on Ungapan Beach is very good, this can be seen from the formation of Pokmas (Community Groups) of Ungapan Beach which actively manages Ungapan Beach tourism by upholding the aspect of accountability openness for the advancement of Ungapan Beach tourism. In addition, the community around Ungapan Beach has begun to improve their economy a lot by establishing businesses in Ungapan Beach tourism, one of which is the establishment of homestays by people whose homes are close to Ungapan Beach.